RENCANA PRODUKSI OLAHAN KOPI DI PERUSAHAAN DAERAH PERKEBUNAN (PDP) KAHYANGAN JEMBER MENGGUNAKAN METODE FUZZY TSUKAMOTO - Yuli Wibowo; Yeyen Retno Maulida; Bambang Herry Purnomo (Agroindustrial Technology, University of Trunojoyo Madura, 2019)
PDP Kahyangan Jember is a regional company owned by the Government of Jember Regency that has agroindustry ground coffee and roasted coffee. The problem is that there was a mismatch between the company's production plan and the number of consumer demand that cause the stock. The impact is that production costs will increase because of the cost of storing and the production process becomes disrupted due to the location of the product storage warehouse in place together with the production space. The purpose of this research is to evaluate and to make a production plan model at PDP Kahyangan Jember. The method used is fuzzy Tsukamoto with input variables in the form of consumer demand and stock. The results showed that the prediction of the quantity of ground coffee and roasted coffee in the past year (July 2017-June 2018) resulted in a MAPE value of 16%. The MAPE value obtained is